2016
DOI: 10.1007/s13203-016-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen: efficient promoter for PNP/Cr(III)/MAO catalyzed ethylene tetramerization toward 1-octene

Abstract: The effect of hydrogen addition on the catalytic activity and product selectivity of PNP/Cr(III)/MAO catalytic systems for ethylene tetramerization was investigated. The results showed that the catalytic activity could be increased twice and the polymer production could be reduced efficiently through hydrogen addition. It could be inferred from the analysis and characterization results of the products that there existed at least three sorts of catalytic active centers in the ethylene tetramerization reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…From the calculations we tested, this reduction in the energy barrier is the only compartment to demonstrate an unquestionable easing effect; hence, we propose that the formation of an active centre is a key factor regarding catalyst activity, thus coinciding with the assumption raised by Jiang et al in 2016 [7] that hydrogen might play an important role in the generation of active centres. In this case, hydrogen reduces the energy barrier to generate active centres on the catalyst; hence, more active centres are available for the reaction, leading to a significant increase in catalyst activity.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…From the calculations we tested, this reduction in the energy barrier is the only compartment to demonstrate an unquestionable easing effect; hence, we propose that the formation of an active centre is a key factor regarding catalyst activity, thus coinciding with the assumption raised by Jiang et al in 2016 [7] that hydrogen might play an important role in the generation of active centres. In this case, hydrogen reduces the energy barrier to generate active centres on the catalyst; hence, more active centres are available for the reaction, leading to a significant increase in catalyst activity.…”
Section: Resultssupporting
confidence: 79%
“…The addition of 2.5 bar of hydrogen to this system alleviated polyethylene formation without much compromise on selectivity and productivity, but the mechanism is unclear. Further investigation regarding this hydrogen‐promoting effect remained scarce until 2016 when Jiang et al [7] confirmed that there is a significant improvement of PNP/Cr(III)/MAO catalyst activity on ethylene tetramerization under hydrogen pressure ranging from 0.03 to 0.50 MPa. A density functional theory (DFT) study of the hydrogen effect on the Chevron‐Phillips trimerization system was conducted by Bahri‐Laleh et al in 2017 [8], in which hydrogen is believed to participate in the reaction and lead to the formation of alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…From the calculations we tested, this reduction of energy barrier is the only compartment to demonstrate an unquestionable easing effect, hence we propose that the formation of active center is a key factor regarding catalyst activity, thus coincide with the assumption raised by Jiang et al in 2016 [6] that hydrogen might play an important role in the generation of active centers. In this case, hydrogen reduces the energy barrier to generate active centers on the catalyst, hence more active centers are available for reaction, leading to the significant increase of catalyst activity.…”
Section: Hydrogen Effect In the Formation Of Active Center On The Catsupporting
confidence: 84%
“…It was noticed then that addition of 2.5 bar of hydrogen to the system alleviated the polyethylene formation without much compromise on selectivity and productivity, but the mechanism is unclear. Further investigation regarding this hydrogen promoting effect remained scarce until 2016 when Jiang et al [6] confirmed that there is a significant improvement of PNP/Cr(III)/MAO catalyst activity on ethylene tetramerization under hydrogen pressure ranging from 0.03 to 0.50 Mpa. A DFT study of hydrogen effect on the Chevron-Phillips trimerization system was conducted by Bahri-Laleh et al at 2017 [7] , in which hydrogen is believed to participate into the reaction and leads to the formation of alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of hydrogen improved the efficiency of catalytic system by decreasing the polyethylene formation and increasing the catalytic activity. Tao Jiang and co-workers also investigated effect of hydrogen addition on the PNP/Cr(III)/MAO catalytic systems in ethylene tetramerization reaction where addition of hydrogen could reduce the molecular weight of polyethylene in addition to reduction in polyethylene formation [30]. The application of hydrogen in commercial plants of ethylene trimerization to reduce the formation of polyethylene can be witnessed from the patent literature [31].…”
Section: Chevron Phillips Cr-pyrrole Catalyst Systemmentioning
confidence: 99%